Ranunculus ternatus Thunb extract attenuates renal fibrosis of diabetic nephropathy via inhibiting SMYD2 - Weiwei Xu; Rui Peng; Siyu Chen; Congcong Wu; Xiaoxiao Wang; Ting Yu; Jiuying Jian; Ni Zhang; Siyang Zuo; Min Chen; Bing Guo; Lirong Liu (Taylor & Francis Group, 2022)
Context Ranunculus ternatus Thunb (Ranunculaceae), (RTT) is used clinically for the treatment of tuberculosis or as tumour adjuvant therapy, but its potential effect on diabetic nephropathy (DN) has not been studied. Objective To investigate the effect of RTT extract in renal fibrosis of DN. Materials and methods C57BL/6 mice were randomly divided into four groups (n = 12). Diabetes mellitus (DM) mice were induced by streptozotocin (STZ, 55 mg/kg/day) for five consecutive days and treated by RTT extract (2 g/kg). Afterward, blood glucose, HE and Masson staining were assayed. The expression levels of Vimentin, ɑ-SMA, TNF-ɑ, NF-κB p-p65, NF-κB p65, SMYD2, H3K36me3, H3K4me3 were determined by western blots. Firbronectin was respectively assayed by western blot and immunofluorescent staining. Results RTT extract significantly ameliorated renal injury and renal fibrosis in the renal tissue of STZ-induced diabetic mice as demonstrated by the decreased expression level of Fibronectin (65%), Vimentin and α-SMA (75% & 53%). In addition, the levels of TNF-α (57%), NF-κB p-p65 and NF-κB p65 (35% & 25%) were elevated in the DN mice. Importantly, these were alleviated after RTT extract treatment. Moreover, we observed that the protein levels of SMYD2 (30%), H3K36me3 and H3K4me3 (53% & 75%) were reduced in DN mice after treatment with RTT extract. Discussion and conclusions RTT extract mediates antifibrotic effects and anti-inflammatory responses in STZ-induced DN mainly through suppressing SMYD2 activation and H3K36me3 and H3K4me3 protein expression. RTT extract might have therapeutic potential against high glucose-induced nephropathy.